Detection of mecA Gene in Methicillin-Resistant Staphylococcus aureus (MRSA) Isolated from Diabetic Ulcer Swab Samples - Aliyya Noor Izzati; Suliati; Lully Hanni Endarini; Syamsul Arifin (International Journal of Advanced Health Science and Technology, 2026)
Diabetic ulcers represent a serious complication of diabetes mellitus, often becoming chronic wounds prone to infection due to impaired immunity, poor vascularization, and persistent hyperglycemia. Among the most frequently identified pathogens in such wounds is Staphylococcus aureus, with methicillin-resistant S. aureus (MRSA) strains posing significant therapeutic challenges due to their resistance to β-lactam antibiotics. This resistance is typically mediated by the mecA gene, which encodes penicillin-binding protein 2a (PBP2a), a protein with reduced affinity for β-lactams. This study aimed to detect the presence of the mecA gene in MRSA strains isolated from diabetic ulcer swabs and to examine the relationship between phenotypic resistance and genotypic confirmation. A total of 30 swab samples were collected from patients with diabetic ulcers at the Diabetes Wound Care Clinic in Surabaya. Bacterial identification was performed using standard microbiological techniques, and cefoxitin disk diffusion was used to screen for MRSA phenotypically. Genomic DNA from cefoxitin-resistant isolates was subjected to conventional PCR using mecA-specific primers, with electrophoresis to detect the expected 304 bp DNA fragment. Of the 30 samples, 19 (63%) were confirmed to be S. aureus, and among them, 6 isolates (31.6%) were resistant to cefoxitin. However, none of these isolates were positive for the mecA gene by PCR, although the positive control showed the expected band. This discrepancy suggests the possibility of other resistance mechanisms beyond mecA, highlighting the importance of molecular methods in confirming MRSA. These findings reinforce the need for integrated phenotypic and genotypic diagnostics to ensure accurate detection and appropriate treatment of MRSA infections